0
votes
1answer
47 views

Prove by Hilbert deduction: ⊢∃x(AvB)→(∃xAv∃xB); ⊢(∃xAv∃xB)→∃x(AvB)

I'd really like your help proving: 1)⊢∃x(AvB)→(∃xAv∃xB) 2)⊢(∃xAv∃xB)→∃x(AvB) Our proof system contains next Hilbert's axioms: 1.A→(B→A) 2.(A→B)→((A→(B→X))→(A→X)) 3.(A&B)→A 4.(A&B)→B ...
1
vote
1answer
61 views

Want to show the a proof of the sequent $\forall x \forall y R(x,y) \Rightarrow R(y,y)$ must have a cut

Want to show the a proof of the sequent $\forall x \forall y R(x,y) \Rightarrow R(y,y)$ must have a cut. For this question we are in the Gentzen calculus. I am even having trouble just finding a ...